EFFICIENT INVESTMENT — THE KEY TO ADVANCED TECHNOLOGIES - Ziyatova Sitora Baxtiyor qizi (Bright Mind Publishing, 2025)
This article analyzes the role of investments in the adoption of modern machinery and technologies. The author highlights the importance of technological modernization in economic development, showing the impact of investments on production efficiency, energy saving, and export potential. Based on research, the role of investments in technological renewal is evaluated with the support of statistical data. The interrelation between foreign investments, innovation financing, and human capital is revealed. The author substantiates the necessity of directing investments not only to technical sectors but also to scientific research, education, and innovation. In conclusion, the article emphasizes the strategic importance of investment policy in achieving technological progress.
Keywords: investment, technological renewal, modern machinery, economic efficiency, foreign capital, innovations, human capital, competitiveness, modernization, investment policy.